2018
DOI: 10.4103/ayu.ayu_176_16
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and anti-inflammatory properties of Plantago ovata Forssk. leaves and seeds against periodontal pathogens: An in vitro study

Abstract: Background: Plantago commonly called as Isabgol ( Plantago ovata Forssk.) is a perennial herb that belongs to the family Plantaginaceae . A range of biological activities has been found from plant extracts, including wound healing activity, anti-inflammatory, analgesic, antioxidant, weak antibiotic, immunomodulating and anti-ulcerogenic activity. Periodontal disease is a complex condition as a result of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Studies have reported that L. usitatissimum has analgesic and anti-inflammatory properties [ 82 ]. The improvement in HRQoL can be accredited to the anti-inflammatory, antioxidant, analgesic [ 14 ] and immunomodulatory [ 83 ] properties of P. ovata . L. usitatissimum has analgesic [ 26 ] and antioxidant properties [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that L. usitatissimum has analgesic and anti-inflammatory properties [ 82 ]. The improvement in HRQoL can be accredited to the anti-inflammatory, antioxidant, analgesic [ 14 ] and immunomodulatory [ 83 ] properties of P. ovata . L. usitatissimum has analgesic [ 26 ] and antioxidant properties [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 • Supplementation of Zinc may alter periodontal disease progression through changes in expression of the ZnT8 transporter gene .12 • Isabgol extract has shown effective antibiotic and weakinflammatory effect by effective action against periodontal pathogens and Matrix metalloproteins. 13 • Omega 3 from polyunsaturated fatty acid act as a signal to prevent neutrophils mediated periodontal tissue damage. 14 • The hydro-alcoholic extract from pomegranate has shown to decrease the Colony Forming Units (CFU'S) per millimeters of dental plaque by 84 % by one minute rinse.…”
Section: Nutrients For Periodontal Healthmentioning
confidence: 99%
“…PO is a naturally occurring compound that possesses benefits including affordability, sustainability, safety profile and accessibility 31 . The PO was first used for purpose of wound healing 32 . Further investigation demonstrated that extract of PO has therapeutic activities including antioxidant, anti-inflammatory, immuno-modulatory and analgesic, among others 33 .…”
Section: Introductionmentioning
confidence: 99%